A gene dysfunction module reveals the underlying pathogenesis of hidradenitis suppurativa: An update. (2nd July 2019) - Li, Xueli; Jiang, Lei; Huang, Yong; Ren, Zhilong; Liang, Xiaoqin; Wang, Peng
Abstract: Hidradenitis suppurativa is a chronic skin disease characterised by repeated skin abscesses with sinus tracts and scar formation. Currently, the aetiology and pathogenesis of hidradenitis suppurativa remain unclear. Genetic factors, immune disorders, hormonal abnormalities, skin‐microbial dysbiosis, smoking, obesity and mechanical friction all influence hidradenitis suppurativa pathogenesis. Moreover, hidradenitis suppurativa has a familial subset with autosomal dominant transmission proposed and is related to a mutation of γ‐secretase component genes. In this review, we analyse and summarise research progress regarding the relationship between the γ‐secretase gene dysfunction and the pathogenesis of hidradenitis suppurativa.